First-line avelumab in a cohort of 116 patients with metastatic Merkel cell carcinoma (JAVELIN Merkel 200): primary and biomarker analyses of a phase II study - D'Angelo, Sandra P.; Lebbe, Celeste; Mortier, Laurent; Brohl, Andrew S.; Fazio, Nicola; Grob, Jean-Jacques; Prinzi, Natalie; Hanna, Glenn J.; Hassel, Jessica C.; Kiecker, Felix; Georges, Sara; Ellers-Lenz, Barbara; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Avelumab (anti-programmed death ligand 1 (PD-L1)) is approved in multiple countries for the treatment of metastatic Merkel cell carcinoma (mMCC), a rare and aggressive skin cancer. We report efficacy and safety data and exploratory biomarker analyses from a cohort of patients with mMCC treated with first-line avelumab in a phase II trial. Methods Patients with treatment-naive mMCC received avelumab 10 mg/kg intravenously every 2 weeks. The primary endpoint was durable response, defined as objective response (complete or partial response; assessed by independent review) lasting >= 6 months. Additional assessments included progression-free survival (PFS), overall survival (OS), safety, and biomarker analyses. Results In 116 patients treated with avelumab, median follow-up was 21.2 months (range: 14.9-36.6). Thirty-five patients had a response lasting >= 6 months, giving a durable response rate of 30.2% (95% CI: 22.0% to 39.4%). The objective response rate was 39.7% (95% CI: 30.7% to 49.2%). Median PFS was 4.1 months (95% CI: 1.4 to 6.1) and median OS was 20.3 months (95% CI: 12.4 to not estimable). Response rates were numerically higher in patients with PD-L1+ tumors, Merkel cell polyomavirus (MCPyV)-negative tumors, and tumors with increased intratumoral CD8(+) T-cell density. Exploratory analyses did not identify a biomarker that could reliably predict a response to first-line treatment with avelumab; however, a novel gene expression signature to identify the presence of MCPyV+ tumors was derived. Treatment-related adverse events (any grade) occurred in 94 (81.0%) patients, including grade 3/4 events in 21 (18.1%) patients; no treatment-related deaths occurred. Conclusion In patients with mMCC, first-line treatment with avelumab led to responses in 40% and durable responses in 30%, and was associated with a low rate of grade 3/4 treatment-related adverse events.